GE_GERICHTE A/647/2011 vom 23. Juni 2011 - GE Cour de justice (2011)
Vente aux enchères. Expertise. Refus débitrice. Défaut motivation. Dénonciation. Irrecevable. | LP.14.2; LP.20.2.3. phr.2; LP.140.3; ORFI.9.2; ORFI.29; ORFI.144